EDUCATION MANAGEMENT AS A TOOL FOR STUDENT CHARACTER BUILDING: A SOCIOLOGY OF EDUCATION PERSPECTIVE - Farihah , Anis; Churahman , Taufik (PT. Antis International Publisher, 2024)
Character education is education aimed at improving the quality and outcome of education that leads to the improvement of a person's potential, talent, abilities through a systematic process in the human form of character. This article aims to explain how sociological science plays a role in building and familiarizing the character of the introverted pupils. Educational sociology is the social science that studies facts, norms, and social deviations, which are key factors in the process of character formation. This research uses a qualitative approach with research methods of library study and research data from sources of literature, journals, and books. In this method, all the data obtained will be analyzed to draw conclusions. The results of this study show that the sociology of education as a branch of the sciences of sociology played an important role in the formation and cultivation of the character of the students who are integrated in the school. Keywords: Sociology